Survival of pediatric patients with ependymoma in a tertiary cancer center in Rio de Janeiro, Brazil - Oigman, Gabriela; Gonzaga, Yung; Christiani, Marcio; Magalhaes, Denise; Moreira, Veronica; Osorio, Diana S.; Ferman, Sima (Frontiers in Oncology, 2024)
Introduction: Ependymoma is the third most frequent central malignant nervous system tumor in pediatric age. There is scarce data in the literature on survival of these patients, especially in upper and lower middle-income countries. We aimed to describe the clinical and demographic characteristics, treatment, and outcome of pediatric patients with ependymoma admitted in a public cancer hospital.Methods: Retrospective analysis of medical records of patients with ependymoma, admitted to the Pediatric Oncology department (0-20 years) during the period of 2000-2022. Data on patient, disease characteristics and treatment were analyzed. Overall survival (OS) was calculated using the Kaplan-Meier method. Results: Seventy-two patients were evaluated, median age at diagnosis was 6,5 years (range: 1-20), 63% were male, 54% of the tumors were in the posterior fossa (PF-EPN), 45% were classified as WHO grade 3, and 68% were operated in other institutions before referral. Regarding treatment, 72% underwent radiotherapy and 33% of patients underwent chemotherapy. Almost 70% percent of the patients had relapses. The median follow-up time was 5.2 years (Range: 0,1-21,4). The OS in 5 years was 67%. Totally resected tumors had OS in 5 years of 88% (p: 0.028). Conclusion: The results achieved in this series show a survival gap between UMIC and HIC. Relapses occurred mainly in the first ten years and then reaching a plateau, with the majority of patients experiencing endocrinological and neurological sequelae.